Pengaruh Profitabilitas dan Ukuran Perusahaan Terhadap Nilai Perusahaan Perbankan Syariah yang Terdaftar di BEI pada Tahun 2019-2023 - Destari, Dea (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
One of the main objectives of a company is to maximize its value. Company value is an investor's perception of the level of success of a company which is often associated with stock prices. This study aims to determine the effect of profitability and company size on the value of Islamic Banking companies listed on the Indonesian Stock Exchange in 2019-2023. Profitability and company size as independent variables while company value as the dependent variable. This study uses secondary data, namely return on assets, total assets, net profit, total equity, number of shares and share prices in Islamic Banking companies listed on the Indonesia Stock Exchange for the period 2019-2023. The sample research method used in this study is purposive sampling, the population in this study is Islamic Banking listed on the Indonesia Stock Exchange. While the research sample is 4 companies quartal 1 to 4 with 80 quarterly data calculated from 2019-2023. Data analysis used in this study is the Descriptive Analysis test and Classical Assumptions and multiple linear regression. The results of the study show that profitability and company size partially have a significant effect on company value with company value. While simultaneously it is known that profitability and company size together have a significant effect on company value. This study is recommended to Islamic banking companies listed on the Indonesia Stock Exchange to further increase profitability. In this case, the company must improve its financial performance and asset capabilities in maximizing company profitability.